2022
DOI: 10.1002/ael2.20094
|View full text |Cite
|
Sign up to set email alerts
|

Sample processing impacts on single wet sieve aggregate stability analysis

Abstract: Soil aggregate stability is widely considered an indicator of soil health. However, there is a lack of test procedure standardization for this soil property. Presently, air‐drying and manual grinding are commonly used in preparing samples for testing, which are time‐consuming and labor intensive. This study evaluated oven‐drying (65 °C) aggregates and processing by either disk or flail mechanical grinders as a way to improve efficiency of conducting aggregate stability analysis as compared with air drying and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…3 & 4; Supplemental Tables S5 & S7). Mechanical grinders are commonly used to sieve and grind soils at commercial labs (Garcia et al, 2022) because they significantly accelerate soil processing time, reducing total costs of analyses (Supplemental Fig. S8).…”
Section: Sievingmentioning
confidence: 99%
See 1 more Smart Citation
“…3 & 4; Supplemental Tables S5 & S7). Mechanical grinders are commonly used to sieve and grind soils at commercial labs (Garcia et al, 2022) because they significantly accelerate soil processing time, reducing total costs of analyses (Supplemental Fig. S8).…”
Section: Sievingmentioning
confidence: 99%
“…Most soil processing methods include a step to sieve air-dried bulk soil and commercial service soil testing labs often utilize a mechanical flail or disk grinder (Garcia et al, 2022) to increase throughput over hand sieving. Based on a survey of 51 soil testing labs, we found that over 70 % use some type of mechanical grinder to sieve (Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 99%